Recent Publications (Quarterly Journal of Economics, 1935)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 49, Issue 3, May 1935, Pages 551–559, https://doi.org/10.1093/qje/49.3.551 Published: 01 May 1935